2015
DOI: 10.1371/journal.pone.0139663
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Landscape of Primary Mediastinal B-Cell Lymphoma Cell Lines

Abstract: Primary mediastinal B-Cell lymphoma (PMBL) is a recently defined entity comprising ~2–10% non-Hodgkin lymphomas (NHL). Unlike most NHL subtypes, PMBL lacks recurrent gene rearrangements to serve as biomarkers or betray target genes. While druggable, late chemotherapeutic complications warrant the search for new targets and models. Well characterized tumor cell lines provide unlimited material to serve as preclinical resources for verifiable analyses directed at the discovery of new biomarkers and pathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 50 publications
3
10
0
Order By: Relevance
“…indicates a constitutive activated JAK2/STAT6 signalling pathway [21]. This can be the consequence of an amplification of the JAK2 gene [22], recurrent mutations of SOCS1 or PTPN1 genes [23][24][25]. In agreement with previous studies, we observed that p-Tyr641-STAT6…”
Section: Discussionsupporting
confidence: 91%
“…indicates a constitutive activated JAK2/STAT6 signalling pathway [21]. This can be the consequence of an amplification of the JAK2 gene [22], recurrent mutations of SOCS1 or PTPN1 genes [23][24][25]. In agreement with previous studies, we observed that p-Tyr641-STAT6…”
Section: Discussionsupporting
confidence: 91%
“…In diffuse large B-cell lymphoma (DLBCL) high COMMD1 expression is correlated with poor prognosis [2] and is associated with aggressive forms of (DLBCL) [42]. Increased COMMD1 expression is also common in primary mediastinal B-cell lymphoma (PMBL) cells lines and in PMBL patients [43]. In contrast, in many other types of cancer (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, neutralizing antibodies directed against CD2 or CD58 prevents conjugate formation and decreases T‐cell activity (Mak & Saunders, ). The CD58 locus in PMBCL was found to be targeted by mono‐ and bi‐allelic microdeletions in 3 of 4 cell lines and in 5 primary tissues interrogated, resulting in conspicuous silencing of CD58 gene expression (Dai et al , ). Although functional studies in PMBCL are lacking, reconstitution of CD58 in a null DLBCL cell line increased NK‐cell mediated cytolysis (Challa‐Malladi et al , ).…”
Section: The Pmbcl Tumour Microenvironmentmentioning
confidence: 99%